The Impact of Financial Metrics on ESG Disclosure in ASEAN Countries - Putra, Donny Maha (ETIKONOMI, 2025)
Research Originality: This study breaks new ground by examining how financial metrics (ROA, ROCE, ETR, SGR, board size) influence ESG disclosure in the unique context of ASEAN.Research Objective: It investigates the relationship between financial performance and ESG disclosure levels for listed companies in Indonesia, Singapore, and Thailand.Research Methods:  Utilizing an in-depth analysis of 300 annual reports over a ten-year period (2011-2020), the study reveals country-specific dynamics.Empirical Results: For instance, Indonesian companies display a weak correlation between effective tax rate (ETR) and ESG disclosure. Conversely, Singaporean companies with higher return on assets (ROA) tend to report less ESG information. Thailand exhibits a more complex interplay, where aggressive tax strategies potentially hinder positive ESG perceptions.Implications: These findings highlight the critical need for tailoring ESG disclosure strategies to each country's financial performance landscape. Additionally, the importance of responsible tax practices is emphasized. This knowledge empowers companies, investors, and policymakers to develop a more targeted approach to ESG implementation across ASEAN.JEL Classification: G32, M14, Q56How to Cite:Putra, D.M. (2025). Impact of Financial Metrics on ESG Disclosure in ASEAN Countries. Etikonomi, 24(1), 85 – 96. https://doi.org/10.15408/etk.v24i1.37712.